JavaScript fundamentals I and II - Deitel, Paul J. (LiveLessons., 2009)
This program will show you how to start building hot new JavaScript and Ajax applications. Watch and learn core JavaScript techniques, including control statements, functions, arrays, objects, events, CSS, and DOM. Then, building on the basics, master scripting with XML and RSS -- and start building the Ajax-rich Internet applications that are taking the Web by storm.